PEMANFAATAN LIMBAH TANAMAN BOKASHI UNTUK BUDIDAYA MELON (Cucumis melo L.) ORGANIK - Nurseha Nurseha; Nurlianti Nurlianti; Septia Yessi Rhamadani; Prihanani Prihanani; Farida Aryani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Bokashi compost is produced through fermentation of organic wastes in an airtight condition using beneficial microbes. This creates a nutrient-rich pre-compost that can be used to enrich the soil. This study investigated the effect of Bokashi type and fermentation age on the growth and yield of organic melon (Cucumis melo L.). A factorial Completely Randomized Design (CRD) with two factors was employed: Bokashi type (oil palm empty fruit bunches, mahogany leaves, and water guava leaves) and fermentation age (1, 5, and 10 months). The results showed that fermentation age significantly affected all observed variables, while Bokashi type significantly influenced flowering time, fruit weight, and fruit diameter. The highest fruit weight (1521.71 g) and diameter (19.07 cm) were obtained from 10-month fermented Bokashi. Among Bokashi types, water guava leaf Bokashi produced the best yield (979.70 g). These findings indicate that extended fermentation improves nutrient availability and enhances melon productivity under organic cultivation systems.